Carbon-coated monoclinic NbOPO4 with polyanionic framework for rechargeable aqueous lithium-ion batteries beyond 2 V. (10th September 2022) - Liu, Junru; Wang, Qiushi; Chen, Liang; Zhang, Jun; Pan, Jiemiao; Wang, Xiaomin; Liu, Zhaoping
Abstract: The choice of anode materials for high-voltage aqueous batteries beyond 1.5 V is still far from satisfactory, due to the narrow electrochemical stability window of aqueous electrolytes. With the inherent advantages of low working voltage and fast ionic diffusion, niobium phosphates with polyanionic framework groups built of NbO6 octahedra and PO4 tetrahedra are very promising anode materials for high-voltage aqueous batteries. Herein, carbon-coated NbOPO4 (NPO/C) materials with monoclinic structure has been prepared by the solid-state reaction & chemical vapor deposition method. Between -1.34 V and 0.6 V vs. standard hydrogen electrode, it could deliver a specific capacity of 116 mAh/g with a high coulombic efficiency of 92.0% at a low current rate of 0.33C in aqueous electrolytes based on methylsulfonylmethane, LiClO4 and H2 O (DES). The diffusion-controlled process dominates the electrochemical reaction of NPO/C. Upon the reversible insertion/extraction of lithium ion into/from NPO/C, it maintains the monoclinic structure with a small lattice expansion, which is a characteristic of zero-strain effect. Finally, the full cell based on NPO/C anode, LiMn2 O4 cathode and DES electrolytes with a high specific energy 101.6 Wh/kg and a high voltage output beyond 2 V has been validated. It also shows excellent cycling performance with the capacity retention of 94.3% after 1000 times at 2C rate, which suggests that monoclinic β-NbOPO4 can be used as a promising electrode material for aqueous lithium-ion batteries with high voltage output for energy storage in the future.